Modelling and Forecasting COVID-19 Stock Returns Using Asymmetric GARCH-ICAPM with Mixture and Heavy-Tailed Distributions - Khanthaporn, Rewat; Wichitaksorn, Nuttanan (Taylor and Francis Group, 2022)
COVID-19 pandemic is an extreme event that created turmoil in stock markets around the world. This unexpected circumstance poses a critical question of whether the prevailing models can help predict the plummets of indices, hence the returns. In this study, we aim to analyse and forecast the daily stock returns using various generalized autoregressive conditional heteroscedastic (GARCH) models with intertemporal capital asset pricing structure and innovation following (1) a mixture of generalized Pareto and Gaussian distributions and (2) generalized error distribution that can capture extreme events. We also employ the parallel griddy Gibbs (GG) sampling, which is a Markov chain Monte Carlo method, to facilitate parameter estimation. Our simulation study shows that the GG estimation method outperforms the benchmark quasi-maximum likelihood estimation method. We then proceed to the empirical study of seven stock markets where the results from the in-sample period before the COVID-19 pandemic justify the use of the proposed GARCH models. The out-of-sample forecasts during the early COVID-19 period also show satisfactory results.
Keywords: 38 Economics; 3801 Applied Economics; 3802 Econometrics; 1402 Applied Economics; 1403 Econometrics; 1502 Banking, Finance and Investment; Economics; 3801 Applied economics; 3802 Econometrics